Workplace Stress as a Predictor of Absenteeism of the Employees of Selected Manufacturing Firms in Lagos State, Nigeria - M. O. Aremo; L. O. Olanipekun; A. M. Ajayi (Kelaniya Journal of Management)
Absenteeism whether voluntary or involuntary is a manifestation of continued stress whose outcome is highly negatively engender poor results as well as low delivery of tasks among employees. One hundred and fifty (150) employees of five selected manufacturing firms in Lagos State served as respondents for the study through purposive and convenience sampling methods. Findings revealed that a significant and positive nexus was found between emotional exhaustion and voluntary absenteeism with “0.743>0.5”; also, a strong and positive correlation existed between psychological consequences and involuntary absenteeism with “0.913>0.5”. The study concluded that activities in the manufacturing environment is massive and has huge propensity to induce stress and high burnout rate thus culminating into high level of work alienation and absenteeism. Therefore, management should on a constant basis lookout for activities that poses stress on employees, such should be given rapt attention and curtailed to avoid work estrangement within and among employees.